PENGARUH KEMUDAHAN DAN KEAMANAN MESIN SELF CHECK-IN TERHADAP KEPUASAN PENUMPANG DI BANDAR UDARA JENDERAL AHMAD YANI SEMARANG - Wahyu Eko Yulianto (Adisam Publisher, 2024)
In the era of modern life, air transportation is very important because it allows people and goods to move to different places quickly and efficiently. Airports are the starting point of the air travel experience and the airport check-in process is one of the important stages of a passenger's journey. The traditional check-in process , which involves long lines at the check-in counter, document checking, ticket printing, and provision of boarding passes, is often time-consuming and inconvenient for passengers. One of the latest innovations introduced in the aviation industry is the automatic self check-in function at the airport, which allows passengers to complete the check-in process independently without direct intervention from airport staff. Airlines and airports around the world have adopted this technology as a solution to reduce long queues at check-in counters, reduce operational costs, and provide a more efficient passenger experience. This research process uses quantitative research methods and is carried out from August to September 2023. In addition, the researcher used a questionnaire as a data collection method and multiple regression analysis method. Passengers at Jenderal Ahmad Yani Airport Semarang are a sample of this study. Based on the T Test, the independent variables of Convenience (X1) and Safety (X2) have a significant influence on the dependent variable of passenger satisfaction (Y) with t calculated > t table (0.240). The F test proves that the variables of convenience (X1) and safety (X2) have a significant influence on passenger satisfaction (Y) with a significance value of 0.000 < 0.05 and the F value of the table (22.173 > 3.14). The Coefficient of Determination (????2) shows that convenience (X1) and safety (X2) affect passenger satisfaction (Y) simultaneously with an Adjusted R Squared value of 0.387 or 38.7% and the remaining 61.3% is influenced by other variable components that are not included or error values.